Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Pendidikan Agama Islam Dengan Media Video di Kelas V UPTD SDN 02 Sarilamak - Riko Putra; Syawaluddin Syawaluddin; Deslita Deslita; Rahma Dani; Titin Ilahi; Indra Femil (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This Classroom Action Research aims to describe efforts to improve the learning outcomes of class V students of UPTD SDN 02 Sarilamak in Islamic Religious Education (PAI) subjects through the use of video media. This research was conducted in two cycles. In each cycle, researchers designed and implemented learning using different video media. Research data were obtained through student learning outcomes tests and observations of student activities during learning. The results showed an increase in the average value of student learning outcomes in each cycle. In addition, observations showed an increase in student motivation and learning activities during the learning process. Thus, it can be concluded that the use of video media is effective in improving student learning outcomes in PAI subjects.